Clinical, neuropathological, and molecular study in two families with spinocerebellar ataxia type 6 (SCA6). Issue 1 (1st July 1999) - Ishikawa, K; Watanabe, M; Yoshizawa, K; Fujita, T; Iwamoto, H; Yoshizawa, T; Harada, K; Nakamagoe, K; Komatsuzaki, Y; Satoh, A; Doi, M; Ogata, T; et al.
Abstract : To clarify the clinical, neuropathological, and molecular characteristics of spinocerebellar ataxia type 6 (SCA6), two unrelated Japanese families with SCA6 were studied. A clinical feature of the two families was late onset "pure" cerebellar ataxia. Pathologically, three SCA6 brains consistently showed Purkinje cell dominant cortical cerebellar degeneration. Morphometric analysis showed that loss of the cerebellar granule cells and inferior olivary neurons were very mild compared with the severity of Purkinje cell loss. There was no obvious ubiquitin immunoreactive nuclear inclusions. All affected patients had identical expanded alleles, and the expansion was also homogeneously distributed throughout the brain without mosaicism. The present study showed that SCA6 is characterised by Purkinje cell dominant cortical cerebellar degeneration, highly stable transmission of the CAG repeat expansion, and lack of ubiquitin immunoreactive nuclear inclusions.